Intraoperative Auditory Assessments as Predictors of Hearing Preservation After Vestibular Schwannoma Surgery - Tucker, Anne; Slattery, William H., III; Solcyk, Linda; Brackmann, Derald E. (Journal of the American Academy of Audiology, 2001)
The purpose of this study was to determine the association of intraoperative auditory brainstem responses (ABRs) and near-field cochlear nerve action potentials (CNAPs) with postoperative hearing preservation in acoustic tumor surgery. Thirty-three consecutive patients undergoing middle fossa surgery had intraoperative surface ABR and direct CNAP assessments. Postoperatively, hearing was assessed. Hearing preservation was defined as any measurable hearing at any frequency and also by the American Academy of Otolaryngology– Head and Neck Surgery (AAO-HNS) hearing preservation classification system. The presence of an ABR or CNAP was associated with hearing preservation and the absence of an ABR, and CNAP was associated with no hearing preservation in 75.6 percent of the cases. The presence of either the ABR or CNAP was not related to AAO-HNS class outcome. ABR and CNAP had a useful rate of prediction of hearing preservation surgery outcome. However, in nearly one-quarter of the cases, no association between ABR or CNAP responses and hearing preservation was found. This finding must be taken into account when determining the clinical usefulness of these techniques.Abbreviations: AAO-HNS = American Academy of Otolaryngology–Head and Neck Surgery, ABR = auditory brainstem response, CNAP = cochlear nerve action potential, Fpz = frontoproximal midline, MRI = magnetic resonance imaging, PTA = pure-tone average, SDS = speech discrimination score
Keywords: Acoustic neuroma; auditory brainstem response; cochlear nerve action potential; vestibular schwannoma